Knowledge and attitudes level of stem cell among registered nurses and undergraduate nursing students in Universiti Sains Malaysia - Leng, Lye Jee (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Stem cell research holds great promise for treatments in many devastating disease of mankind. Study suggests that stem cell research is an important scientific breakthrough to intervene in medicine and bringing hope in terms of quality of life. Registered nurses and nursing students need to understand stem cell research so they can translate information on this issue. The aim of this study was to investigate the knowledge of stem cells, attitudes toward the application in medical setting among Neonatal Intensive Care Units (NICUs) and Obstetrics and Gynecology Wards registered nurses in Hospital Universiti Sains Malaysia (HUSM) and undergraduate nursing students in Universiti Sains Malaysia (USM). A cross-sectional study was conducted on registered nurses (RNs) and undergraduate nursing students in the Health campus, USM after ethics approval was obtained. Simple random sampling was used to select the sample. Ninety seven (RNs) and 88 undergraduate nursing students were involved in this study. Data were collected using self-administered questionnaire developed by the researcher according to the literature. The questionnaire included demographic characteristics of respondents and 20 knowledge questions and 10 attitude statements on stem cell application in medical setting. Data was analyzed using the Statistical Package Social Science (SPSS) software version 20.0. The results showed that most respondents had moderate knowledge on stem cell, nevertheless, Independent T-test revealed that registered nurses were more knowledgeable regarding stem cells, with a mean score of 32.6, compared to the undergraduate nursing students, with mean scores of 31.7 (p<0.05). There was no significant difference in attitude among the registered nurses and undergraduate nursing students (p>0.05). Most of the respondents are worried about stem cell treatments, nevertheless they see the future of stem cell treatment and agree that more exposure should be given to them. Using the correlation coefficient, it was shown that there was a fair relationship (r=0.26) between the employment years and knowledge of stem cells for RNs. On the other hand, there seem to show poor relationship (r=0.02) between the educational years and knowledge of stem cells for the undergraduate nursing students. In conclusion, this study suggests that both groups of participant, whether RNs or undergraduate nursing students (future nurses) lack stem cell knowledge that is essential for daily practices. This moderate knowledge affects their attitude in delivering stem cell issues and information. Therefore, review of curriculum and continuous nursing education on stem cells information is suggested.